'A General Insurrection in the Countries with Slaves': The US Civil War and the Origins of an Atlantic Revolution, 1861–1866. Issue 1 (31st December 2021) - Payne, Samantha
Abstract: This article reveals how the beginning of US Reconstruction precipitated a revolutionary crisis in Cuba and Brazil, the last two slave societies in the Atlantic World. Throughout the US Civil War, slave-owners in Cuba and Brazil faced the immense challenge of containing black revolutionary currents across the Atlantic. Despite their intensive policing of black transnational networks, many slaves in Cuba and Brazil learned of the Civil War and became convinced that it heralded their emancipation. In response, they walked off plantations, fled to maroon communities, and organized and launched revolts. Although the scale of this insurrectionary violence never reached the same heights as in the Confederacy, the beginning of Reconstruction transformed the political implications of slave rebellion across the hemisphere. The fall of the Confederacy forced slave-owners in Cuba and Brazil to confront the possibility of their violent destruction at the same moment that the apparent radicalization of Republican politics stirred fears of US support for an international slave insurrection. It was in this context that many white elites in both nations became convinced of the necessity for a gradual abolition measure, which they hoped would ensure subaltern loyalty at a moment when revolutionary violence threatened the future of slavery.